Bruton's tyrosine kinase inhibitors: first and second generation agents for patients with Chronic Lymphocytic Leukemia (CLL). (2nd January 2018) - Thompson, Philip A; Burger, Jan A
ABSTRACT: Introduction : The BTK inhibitor ibrutinib is effective in both low- and high-risk CLL patients, achieving durable remissions with continuous therapy in the majority of patients. Ibrutinib lacks myelotoxicity and is generally well tolerated by older and unfit patients; however, side effects, such as atrial fibrillation or hemorrhage, can result in treatment interruption or discontinuation. Given the high efficacy and overall safety, ibrutinib is increasingly used in untreated and previously treated CLL patients. Second-generation BTK inhibitors are being developed, with different and generally more BTK-selective kinase inhibition profiles, which may increase the safety and/or efficacy. Areas covered : We review key features of ibrutinib, along with problems of its use, discuss the potential and drawbacks of second generation molecules, and discuss combination therapies currently in development. Expert Opinion : BTK inhibitors have been a major therapeutic advance in older/unfit patients and those with high-risk and/or relapsed CLL, but require indefinite maintenance therapy and risk of developing treatment resistance or adverse events requiring treatment cessation increases over time. Novel combination strategies are currently being evaluated (e.g. the combination of ibrutinib with venetoclax), which may achieve greater depth of remission, remove the need for indefinite maintenance treatment and potentially replace chemoimmunotherapy in the first-line setting.